Skull sinuses precluded extinct crocodile relatives from cetacean-style deep diving as they transitioned from land to sea - Young, Mark T. (2024)
During major evolutionary transitions, groups develop radically new body plans and radiate into new habitats. A classic example is cetaceans which evolved from terrestrial ancestors to become pelagic swimmers. In doing so, they altered their air-filled sinuses, transitioning some of these spaces to allow for fluctuations in air capacity and storage via soft tissue borders. Other tetrapods independently underwent land-to-sea transitions, but it is unclear if they similarly changed their sinuses. We use computed tomography to study sinus changes in thalattosuchian crocodylomorphs that transformed from land-bound ancestors to become the only known aquatic swimming archosaurs. We find that thalattosuchian braincase sinuses reduced over their transition,similar to cetaceans, but their snout sinuses counterintuitively expanded, distinct from cetaceans,and that both trends were underpinned by high evolutionary rates. We hypothesize that aquatic thalattosuchians were ill suited to deep diving by their snout sinuses, which seem to have remained large to help drain their unusual salt glands. Thus, although convergent in general terms, thalattosuchians and cetaceans were subject to different constraints that shaped their transitions to water. Thalattosuchians attained a stage similar to less pelagic transitional forms in the cetacean lineage (late protocetid-basilosaurid) but did not become further specialized for ocean life.